Analyzing the Impact of Macro-Economic Factors and Taxation Manoeuvre on Federal Budget Revenues in the Russian Federation - E. S. Inozemtcev; O. V. Kochetygova; M. A. Katkova (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The article studies the impact of macro-economic factors, such as the US dollar rate, inflation rate, changes in the physical volume of export, drop in world prices on oil and alteration of taxation and customs legislation of the Russian Federation on revenues of the federal budget. The authors use the integral factor analysis of the absolute growth in federal budget revenues in Russia in assumption of simultaneous changes in factors on the indicator function. Conventional methods of determinate factor analysis, including the method of chain substitution imply successive change in factors. The authors conducted qualitative estimation of the absolute growth (decline) in federal budget revenues in the Russian Federation under the influence of selected macro-economic factors and changes in taxation and customs legislation, while in conventional research only changes in factors themselves are estimated. They came to the conclusion about the insufficient compensation for the decline in customs duties on oil and oil products by the increase in tax on minerals extraction. The growth in budget revenues was shown at the expense of administrative control strengthening but not at the expense of economic growth. Recommendations were put forward aimed at the increase in investment activity through changing the procedure of depreciation charges and using resources of the foundation of national welfare.